Two flat-backed polydesmidan millipedes from the Miocene Chiapas-amber Lagerstätte, Mexico. - Francisco Riquelme (Public Library of Science (PLoS), 2014)
Two species of fossil polydesmidan millipedes (Diplopoda: Polydesmida) embedded in amber are described from Miocene strata near Simojovel, in the Chiapas Highlands, Mexico. Maatidesmus paachtun gen. et sp. nov., placed into Chelodesmidae Cook, 1895, and Anbarrhacus adamantis gen. et sp. nov., assigned in the family Platyrhacidae Pocock, 1895. Morphological data from fossil specimens have been recovered using 3D X-ray micro-computed tomography and regular to infrared-reflected microscopy. Both fossil species are recognizable as new primarily but not exclusively, by collum margin modification and remarkable paranotal and metatergite dorsal sculpture.